2003
DOI: 10.1021/ma035592v
|View full text |Cite
|
Sign up to set email alerts
|

Complex Macromolecular Architectures Utilizing Metallocene Catalysts

Abstract: Graft copolymers having poly(methyl methacrylate), PMMA, backbone and polystyrene, PS, polyisoprene, PI, poly(ethylene oxide), PEO, poly(2-methyl-1,3-pentadiene), P2MP, and PS-b-PI branches were prepared using the macromonomer methodology and high-vacuum techniques. The methacrylic macromonomers, mMM, were synthesized by anionic polymerization, whereas their homopolymerization and copolymerization with MMA were performed by metallocene catalysts. Relatively high macromonomer conversions were obtained in all ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 43 publications
0
17
0
3
Order By: Relevance
“…This behavior can be attributed to the low polymerization ability of c HMA and TMSiOEMA, as previously mentioned, bearing in mind that the active center is sterically hindered by the presence of the bulk ligand (PMMA chain) of the zirconocene complex. Similar problems have been encountered in the synthesis of PMMA‐ b ‐P n BuMA block copolymers starting from the polymerization of MMA 9. Consequently, the sequence of monomer addition was reversed, starting from the polymerization of c HMA or TMSiOEMA, followed by the addition of MMA.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…This behavior can be attributed to the low polymerization ability of c HMA and TMSiOEMA, as previously mentioned, bearing in mind that the active center is sterically hindered by the presence of the bulk ligand (PMMA chain) of the zirconocene complex. Similar problems have been encountered in the synthesis of PMMA‐ b ‐P n BuMA block copolymers starting from the polymerization of MMA 9. Consequently, the sequence of monomer addition was reversed, starting from the polymerization of c HMA or TMSiOEMA, followed by the addition of MMA.…”
Section: Resultsmentioning
confidence: 85%
“…The crucial parameter defining the success of the synthetic procedure lies in the addition sequence of the monomers. Earlier studies9, 15 have shown that during the synthesis of MMA block copolymers with other methacrylates, the procedure is not successful when MMA is polymerized first. This behavior can be attributed to the slower polymerization rate of the second monomer, which enables side reactions, thus terminating many or even all of the growing chains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, PP with long grafted chains has become one of the major themes in recent PP modification research 2–6, 8–15. Up to now, several approaches have been developed to prepare branched PP, including high‐energy electron‐beam irradiation,10, 12, 14 peroxide curing,16, 17 azide coupling,18 and in‐reactor metallocene copolymerization of propylene with in situ generated or externally added macromonomers 2, 4, 6, 11, 19–25. For example, several research groups13, 22, 26, 27 have reported the synthesis of long‐chain‐branched PP by the copolymerization of propylene and macromonomers, such as atactic PP, polyethylene, or poly(ethylene‐ co ‐propylene) macromonomers.…”
Section: Introductionmentioning
confidence: 99%